Probing non-standard top-quark couplings via optimal-observable analyses at LHC - Hioki Zenrō; Ohkuma Kazumasa (EPJ Web of Conferences, 2013)
Focusing attention on top-quark pair production and its decay processes at the LHC, non-standard top-quark couplings are studied based on the effective Lagrangian constructed with SU(3)×SU(2)×U(1) invariant dimension-6 operators. The optimal-observable analysis is carried out for the charged-lepton distributions in pp → tt̅X → ℓ +X' (ℓ = e or μ) in order to estimate the expected statistical uncertainties in measurements of those non-standard tt̅g and tbW couplings that contribute to this process in the leading order.